Studi tentang Variabel Kepemimpinan, Komitmen Organisasi dan Intensi Turnover - Rahayu Mardikaningsih; Misbachul Munir (Journal of Trends Economics and Accounting Research, 2021)
Human resources are needed to support the continuity of the company, especially to achieve the goals and vision of the company. Leadership and commitment are needed by the company in order to lead to the vision that already exists and is developed. This study examines the effect of leadership and commitment on turnover intentions of employees in Surabaya. With the number of samples used is 70 respondents, the test to be carried out is using the validity test, reliability test, normality test and the analysis tool used is multiple linear regression analysis. The results obtained are that leadership affects turnover intentions. The better the leadership, the lower the turnover intention. Likewise, commitment has an effect on turnover intention. An employee must have a commitment to get good performance which will reduce turnover intention.